The inclusion of Roma, Sinti and Caminanti at school: the "Inclusive Profile" to understand the classroom climate - Diego Di Masi; Ombretta Zanon (University of Bologna, 2017)
The paper presents the "inclusive classroom profile", an operational proposal to observe and evaluate the relationship among peers in the classroom. The inclusive classroom profile has been designed and tested within the national project for the inclusion and integration of Roma children funded by the Ministry of Labour and Social Policy and coordinated by the Florence-based Istituto degli Innocenti (2013-2016). The inclusive profile has been developed to assess the effects of cooperative methodologies on the inclusion of Roma children in school, using data collected with "sociometric questionnaires" and "classroom drawings". The aim is to introduce research practices in school to overcome the "naive pedagogy" about group dynamics, using tools to analyze "hidden" variables and to share points of view among teachers. The inclusive profile has been used by teachers to monitor, evaluate and plan educational activities taking into account child's perspective.